(untitled) (American Journal of Islam and Society, 2022)
The historical interaction between Muslims and their non-Muslim subjects and neighbors is a topic of interest for many scholars who are interested in the potential for positive interreligious coexistence past and present. Several recent books speak to different aspects of this relationship with a particular focus on Christians living under the rule of the early Muslims. These include Jack Tannous’s The Making of the Medieval Middle East (Princeton University Press, 2018), a broad look at the transition from Christian to Muslim rule in the region, and Christian Sahner’s Christian Martyrs under Islam (Princeton University Press, 2020), which focuses more specifically on the phenomenon of martyrdom. In line with the more tightly contained scope of the latter work, Bradley Bowman’s new book takes a close look at Christian monks in the Middle East and their interactions with the new societal structures and ideologies of Islam.